1998
DOI: 10.1159/000013975
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide neither Alters Oxidative Stress Parameters nor Induces Lung Inflammation in Premature Lambs with Moderate Hyaline Membrane Disease

Abstract: The purpose of this investigation was to examine whether inhaled nitric oxide (NO) may alter oxidative stress parameters and induce lung inflammation in moderate hyaline membrane disease (HMD). Eighteen moderately premature lambs (130 days gestation, term = 147 days) were randomly assigned to treatment with 20 ppm inhaled NO (n = 8) from the onset of ventilation or used as control (n = 10). Except inhaled NO, treatments were intentionally similar to those applied in clinical situations. The main studied parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In lambs delivered at 130 days gestation and mechanically ventilated for 5 hours with INO, there was no evidence of lung oxidative stress injury (lung malondialdehyde, reduced glutathione, glutathione reductase) compared to controls [16]. This finding is consistent with other studies on the role of INO in reducing oxidant stress [17][18][19].…”
Section: Rationale For Inhaled Nitric Oxide Therapy In the Premature supporting
confidence: 89%
“…In lambs delivered at 130 days gestation and mechanically ventilated for 5 hours with INO, there was no evidence of lung oxidative stress injury (lung malondialdehyde, reduced glutathione, glutathione reductase) compared to controls [16]. This finding is consistent with other studies on the role of INO in reducing oxidant stress [17][18][19].…”
Section: Rationale For Inhaled Nitric Oxide Therapy In the Premature supporting
confidence: 89%
“…11 The mechanism of action of ADM is not completely understood, but it probably depends only partially on NO pathway. 12,13 Moreover, previous studies demonstrated that iNO can promote [13][14][15][16][17] or attenuate [18][19][20] inflammatory and oxidative lung injuries, and affect surfactant function; [21][22][23] PGI 2 can contribute to decrease inflammatory processes 24 and oxidative cell damage; 25 and, finally, ADM can act as both pro-inflammatory and anti-inflammatory agent, [26][27] and decrease the oxidative cell stress. 28 Based on the above observations, we hypothesized that PH treatment with combined inhalation of both iNO plus PGI 2 , and iNO plus ADM might be more effective in lowering PAP and improving oxygenation than iNO alone.…”
Section: Introductionmentioning
confidence: 99%
“…Finding the optimal time for beginning iNO therapy is of the utmost importance since this factor might limit the duration of mechanical ventilation and oxygen therapy, which increase the risk of BPD promoting pulmonary inflammation [28][29][30][31][32] and oxidative damage [33][34][35][36] . In other words, the earlier the iNO therapy is started, when the lungs are less injured, the more effective BPD prevention might be.…”
Section: Optimal Age Dose and Duration Of Ino Therapymentioning
confidence: 99%
“…Moreover, iNO treatment was associated with greater dynamic lung compliance, and decreased expiratory resistance. It is likely, therefore, that the beneficial effects of iNO on pulmonary function in this model of chronic lung disease reflect primarily nonsurfactant actions, such as anti-inflammatory [27][28][29][30][31] and antioxidant actions [32][33][34][35] . These results are in agreement with the observation that iNO increases lung compliance and tidal volume, and decreases airway resistance, without affecting surfactant surface activity in an animal model of acute lung injury [56] .…”
Section: Ino Therapy and Surfactantmentioning
confidence: 99%
See 1 more Smart Citation